Indigo - Bass, Ellen (Copper Canyon Press, 2020)
"Indigo, the newest collection by Ellen Bass, merges elegy and praise poem in an exploration of life's complex grey areas. Whether her subject is oysters, high heels, a pork chop, a beloved dog, or a wife's return to health, Bass pulls us in with exquisite immediacy. Her lush and precisely observed descriptions allow us to feel the sheer primal pleasure of being alive in our own "succulent skin," the pleasure of the gifts of hunger, desire, touch. In this book, joy meets regret, devotion meets dependence, and most importantly, the poet so in love with life and living begins to look for the point where the price of aging overwhelms the rewards of staying alive. Bass is relentless in her advocacy for the little pleasures all around her. Her gaze is both expansive and hyperfocused, celebrating (and eulogizing) each gift as it is given and taken, while also taking stock of the larger arc. She draws the lines between generations, both remembering her parents' lives and deaths and watching her own children grow into the space that she will leave behind. Indigo shows us the beauty of this cycle, while also documenting the deeply human urge to resist change and hang on to the life we have, even as it attempts to slip away"--